Teachers’ Experience of ICT Training for Professional Development - Gautam, Krishna (Kalika Journal of Multidisciplinary Research, 2023)
This article discusses on teachers’ experience of Information and Communication Technology training for their professional development and in teaching and learning in the context of Nepal. It also discusses the policy documents which are brought to train the teachers focusing on the use of ICT in teaching and learning highlighting the problems that appear to implement the IT policies and teachers’ professional development. It also examines the teachers’ knowledge of ICT and their perception of using it in teaching. This study was based on a qualitative interpretive design that follows the semi-structured interviews with the participants and observation of schools to find out the teachers’ experiences of using technology for their professional development and the availability of IT resources, and tools at schools. The findings indicate that most of the teachers are not trained in ICT for their professional development and some of the teachers have taken TPD training in which there is not any association of information and communication technology. Teachers are so curious to learn Technology for their professional development but the lack of teacher training is the main problem. This study was carried out to find out the existing practices of using new technology for professional development which resulted in teaching and learning. Although this is a small study, this provides insights to fill the gap between training policy and the problems that exist at the practice level which will be helpful to improve education in Nepal.